The Romance Inter-Views: Syntax - Grant Armstrong; Karlos Arregi; Karen De Clercq; Caterina Donati; Antonio Fábregas; Luigi Rizzi; Andrés Saab; Norma Schifano (Isogloss, 2021)
The Romance Inter-Views are short, multiple Q&A pairs that address key issues, definitions and ideas regarding Romance linguistics. Prominent exponents of different approaches to the study of Romance linguistics are asked to answer some general questions from their viewpoint. The answers are then assembled so that readers can get a comparative picture of what’s going on in the field.